TRANSGENIC TOBACCO PLANTS EXPRESSING YEAST-DERIVED INVERTASE IN EITHER THE CYTOSOL, VACUOLE OR APOPLAST - A POWERFUL TOOL FOR STUDYING SUCROSE METABOLISM AND SINK SOURCE INTERACTIONS - Sonnewald, Uwe; et al. (Plant Journal, 1991)
Transgenic tobacco plants expressing the yeast-derived invertase in different subcellular compartments displayed dramatic phenotypic differences when compared to wild-type plants. All transgenic plants showed stunted growth accompanied by reduced root formation. Starch and soluble sugars accumulated in leaves indicating that the distribution of sucrose was impaired in all cases. Expression of cytosolic yeast invertase resulted in the accumulation of starch and soluble sugars in both very young (sink) and older (source) leaves. The leaves were curved, indicating a more rapid cell expansion or cell division at the upper side of the leaf. Light-green sectors with reduced photosynthetic activity were evenly distributed over the leaf surface. With the apoplastic and vacuolar invertase, the phenotypical changes induced only appear in older (source) leaves. The development of bleached and/or necrotic sectors was linked to the source state of a leaf. Bleaching followed the sink to source transition, starting at the rim of the leaf and moving to the base. The bleaching was paralleled by the inhibition of photosynthesis.